2022
DOI: 10.1155/2022/2724515
|View full text |Cite
|
Sign up to set email alerts
|

ARL4C Regulates the Progression of Clear Cell Renal Cell Carcinoma by Affecting the Wnt/β-Catenin Signaling Pathway

Abstract: Purpose. To investigate the expression of the ADP-ribosylation factor (ARF)-like proteins (ARLs) and ARL4C in clear cell renal cell carcinoma (ccRCC) based on bioinformatics analysis and experimentally determine the effect and mechanism of ARL4C on cellular properties involved in ccRCC progression. Methods. After downloading the data of cancer patients from the TCGA database, we used various bioinformatics analysis websites and methods to analyze the expression and function of ARLs and ARL4C. The differential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Regarding the function of ARL4C, the expression of ARL4C controls the activation of Rac, the inhibition of Rho and the nuclear localization of YAP and TAZ in HCT116 colon cancer cells and A549 lung adenocarcinoma cells 108 . Consistently, ARL4C‐depleted tumor cells, including HCT116, A549, NCI‐H520 lung SCC cells, HLE HCC cells, H1975 lung adenocarcinoma cells, AGS gastric cancer cells, S2‐CP8 pancreatic cancer cells and ACHN clear cell renal cell carcinoma cells, exhibited reduced migration, invasion and proliferation capabilities both in vitro and in vivo 108,109,114–116,120,121 . In addition, ARL4C reportedly enhances the rate of cholesterol efflux in HeLa cells, 122 a human cervical carcinoma cell line, and is involved in the transport of transferrin from early endosomes to recycling endosomes by interacting with α‐tubulin in human renal carcinoma cells 123 …”
Section: Arl4c In Tumorsmentioning
confidence: 84%
See 1 more Smart Citation
“…Regarding the function of ARL4C, the expression of ARL4C controls the activation of Rac, the inhibition of Rho and the nuclear localization of YAP and TAZ in HCT116 colon cancer cells and A549 lung adenocarcinoma cells 108 . Consistently, ARL4C‐depleted tumor cells, including HCT116, A549, NCI‐H520 lung SCC cells, HLE HCC cells, H1975 lung adenocarcinoma cells, AGS gastric cancer cells, S2‐CP8 pancreatic cancer cells and ACHN clear cell renal cell carcinoma cells, exhibited reduced migration, invasion and proliferation capabilities both in vitro and in vivo 108,109,114–116,120,121 . In addition, ARL4C reportedly enhances the rate of cholesterol efflux in HeLa cells, 122 a human cervical carcinoma cell line, and is involved in the transport of transferrin from early endosomes to recycling endosomes by interacting with α‐tubulin in human renal carcinoma cells 123 …”
Section: Arl4c In Tumorsmentioning
confidence: 84%
“…108 Consistently, ARL4C-depleted tumor cells, including HCT116, A549, NCI-H520 lung SCC cells, HLE HCC cells, H1975 lung adenocarcinoma cells, AGS gastric cancer cells, S2-CP8 pancreatic cancer cells and ACHN clear cell renal cell carcinoma cells, exhibited reduced migration, invasion and proliferation capabilities both in vitro and in vivo. 108,109,[114][115][116]120,121 In addition, ARL4C reportedly enhances the rate of cholesterol efflux in HeLa cells, 122 a human cervical carcinoma cell line, and is involved in the transport of transferrin from early endosomes to recycling endosomes by interacting with α-tubulin in human renal carcinoma cells. 123 The expression of ARL4C as a molecular target for anti-cancer therapy…”
Section: The Function Of Arl4c In Cancersmentioning
confidence: 99%
“…Another study demonstrated that the downregulation of ARL4C significantly inhibits the proliferation, migration and invasion of clear cell renal cell carcinoma cells. Moreover, ARL4C promoted the progression of clear cell renal cell carcinoma and the occurrence of epithelial-mesenchymal transformation (EMT) ( 39 ). By contrast, other studies have showed that ARL4C is a tumour suppressor in ovarian and breast cancer and low expression of ARL4C was associated with poor prognosis in these patients ( 40 , 41 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al ( 50 ) reported that the PI3K/AKT/mTOR signalling pathway is an important regulator of the proliferation, migration and invasion of LoVo colon cancer cells. Previous studies demonstrated that the regulation of ARL4C expression is involved in multiple carcinogenic signalling pathways, such as Wnt/β-catenin ( 39 ), p53 ( 13 ), RAF1-MEK/ERK ( 51 ) and AKT/mTOR ( 34 ). In the present study, AKT or mTOR inhibitors regulated ARL4C protein expression in HCT-116 and SW480 colon cancer cells, which further identifies the critical role of AKT in regulating the ARL4C protein.…”
Section: Discussionmentioning
confidence: 99%
“…Another malignant urological tumor is renal cancer, although only one study has evaluated function of Wnt in the modulation of metastasis. In this case, Wnt increases levels of ARL4C to enhance cyclin D1 and c-Myc levels, leading to EMT induction and enactment in progression of tumor cells [ 120 ].…”
Section: Wnt/β-catenin Signaling As a Regulator Of Emt In Human Cancersmentioning
confidence: 99%